טיכה והמלאכים היושבים: שלושה קמעות בארמית יהודית-גלילית - אליצור-ליימן רבקה; בוהק גדעון (מחשבת ישראל, 2025)
This paper publishes three Jewish Palestinian Aramaic amulets dating from the fifth to seventh centuries CE. Though originating from different contexts, they share a distinctive angelological formula invoking angels who “sit” in various cosmic locations to restrain demons emerging from the heavens, earth, waters, and the abyss. One amulet also appeals to Tyche, the Greek goddess of fortune, alongside the Jewish God and His angels, reflecting the interaction between Jewish and Greco-Roman religious traditions. Through philological and comparative analysis, the study explores the “angels who sit” formula, situating it within the broader cultural context. The discussion traces the development and adaptation of this formula across time and language, from its late antique manifestations to its echoes in medieval Ashkenazi sources.